Thermodynamic Modeling of Hydrogen Storage Capacity in Mg-Na Alloys - S. Abdessameud; M. Mezbahul-Islam; M. Medraj (The Scientific World Journal)
Thermodynamic modeling of the H-Mg-Na system is performed for the first time in this work in order to understand the phase relationships in this system. A new thermodynamic description of the stable NaMgH3 hydride is performed and the thermodynamic models for the H-Mg, Mg-Na, and H-Na systems are reassessed using the modified quasichemical model for the liquid phase. The thermodynamic properties of the ternary system are estimated from the models of the binary systems and the ternary compound using CALPHAD technique. The constructed database is successfully used to reproduce the pressure-composition isotherms for MgH2 + 10 wt.% NaH mixtures. Also, the pressure-temperature equilibrium diagram and reaction paths for the same composition are predicted at different temperatures and pressures. Even though it is proved that H-Mg-Na does not meet the DOE hydrogen storage requirements for onboard applications, the best working temperatures and pressures to benefit from its full catalytic role are given. Also, the present database can be used for thermodynamic assessments of higher order systems.